Direct vs indirect measurement of the effective electronic temperature in quantum dot solids - Kompatscher, Anton; Shokrani, Morteza; Feurstein, Johanna; Kemerink, Martijn (The journal of physical chemistry. C, Energy, materials, and catalysis, 2025)
One of the characteristics of disordered semiconductors is the slow thermalization of charge carriers after excitation due to photoabsorption or high electric fields. An elegant way to capture the effects of the latter on the conductivity is through a field-dependent effective electronic temperature Teff that can significantly exceed that of the lattice. Despite its elegance, its actual use has been limited, which, at least in part, can be attributed to the concept originating from computer simulations; experimental confirmations have largely been indirect (through scaling of conductivity) and did not establish that Teff equals the real temperature of the electron distribution. Moreover, it has hardly been tested for important classes of disordered materials, including quantum dot solids. Here, we investigate whether the effective temperature concept is applicable to quantum dot solids, using zinc oxide as relevant model system. To verify that field-driven conductivity increases indeed reflect an actual increase of the electronic temperature, we combine direct and indirect measurements of Teff: we convert conductivity changes at high fields to an effective temperature that we show to be consistent with a direct measurement of the electronic temperature using the Seebeck effect. These results not only confirm the relevance of the effective temperature concept to quantum dot solids but also confirm its general physical reality and open the way to systematic investigations into charge carrier (de)localization in disordered media.